EROICA / ERARD - Montebugnoli, Luca; Beghin, Tom (Ghent Orpheus Insituut, 2024)
Video recording of the album "EROICA / ERARD"Abstract:October 1803: On hearing Beethoven play the Eroica symphony on his new Erard Frères piano, a witness remarked, “Heaven and Earth must shake at its performance.” Inspired by this historical scene, Luca Montebugnoli has created a new arrangement of the symphony tailored to a unique replica of Beethoven’s Erard. By delivering a novel interpretation of an iconic work, Montebugnoli revives the neglected art of piano arrangement, while also exploring the full potential of what was in Beethoven’s life a revolutionary instrument.Program:- Joseph Haydn, Die Schöpfung, Hob. XXI:2, Einleitung: Die Vorstellung des Chaos, Largo, arranged by Daniel Steibelt- Ludwig van Beethoven, Symphony No. 3 in E-flat major, op. 55, “Eroica”, arranged by Luca MontebugnoliInstrument:Replica of Beethoven’s Erard Frères piano en forme de clavecin (Paris, 1803), by Chris Maene (Ruiselede, 2016)
FRIS
0
Keywords: Beethoven, Ludwig van -- 1770-1827; Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850; Arrangement; Historically informed performance; Piano